A walk-in clinic for newly arrived mentally burdened refugees: the patient perspective - Zehetmair, Catharina; Zeyher, Valentina; Cranz, Anna; Ditzen, Beate; Herpertz, Sabine; Kohl, Rupert Maria; Nikendei, Christoph (International journal of environmental research and public health, 2021)
Providing refugees with psychosocial support is particularly important considering the high level of mental health problems prevalent in this population. A psychosocial walk-in clinic operating within a state reception and registration center in Germany has been supporting mentally burdened refugees since 2016. This study focused on patients’ perspectives on their mental health burden, the psychosocial walk-in clinic, and future help seeking. We conducted interviews with n = 22 refugees attending the walk-in clinic from March to May 2019. Qualitative analysis focused on the following four topics: (1) mental burden from the patients’ perspective, (2) access to the psychosocial walk-in clinic, (3) perception of counseling sessions, and (4) perception of follow-up treatment. The results show that the majority of interviewees were burdened by psychological and somatic complaints, mostly attributed to past experiences and post-migratory stress. Therapeutic counseling and psychiatric medication were found to be particularly helpful. Most of the participants felt motivated to seek further psychosocial support. Key barriers to seeking psychosocial help included shame, fear of stigma, and lack of information. Overall, the psychosocial walk-in clinic is a highly valued support service for newly arrived refugees with mental health issues.
Gesehen am 06.08.2021